2023
DOI: 10.3389/fpls.2023.1273546
|View full text |Cite
|
Sign up to set email alerts
|

Sustained organic amendments utilization enhances ratoon crop growth and soil quality by enriching beneficial metabolites and suppressing pathogenic bacteria

Nyumah Fallah,
Ziqin Pang,
Zhaoli Lin
et al.

Abstract: IntroductionOrganic soil amendments such as filter mud (FM) and biochar (BC) can potentially influence the abundance and composition of metabolites. However, our current understanding of the stimulatory effects of FM and BC’s long-term impact on stress-regulating metabolites, such as abscisic acid (ABA), jasmonic acid (JA), melatonin, and phenyllactic acid (PLA), and these substrates regulatory effects on disease-causing bacteria in sugarcane ratooning field, which is susceptible to nutrients depletion, diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Our investigation showed that ABA exhibited a linear increase in both PR25 and AR2640, exhibiting the highest peak 22 d after harvest, especially at low stubble heights, corroborating He et al's work [43], wherein they documented that ABA was responsible for ratoon rice panicle regeneration. This behavior confirms Fallah et al's recent findings, wherein they mentioned that ABA enrichment contributed to the promotion of sugarcane ratoon crop growth [41].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our investigation showed that ABA exhibited a linear increase in both PR25 and AR2640, exhibiting the highest peak 22 d after harvest, especially at low stubble heights, corroborating He et al's work [43], wherein they documented that ABA was responsible for ratoon rice panicle regeneration. This behavior confirms Fallah et al's recent findings, wherein they mentioned that ABA enrichment contributed to the promotion of sugarcane ratoon crop growth [41].…”
Section: Discussionsupporting
confidence: 91%
“…A large body of studies have reported that ABA serves many vital functions in plants, including growth regulation, stress response, and leaf senescence [40]. For instance, a recent study mentioned that a number of crucial plant hormones, including ABA and jasmonic acid, contributed to the promotion of sugarcane ratoon crop growth and soil quality [41]. In a related study, the ABA content in rice crops increased steadily, triggering a sharp increase in the crop panicle weight 20 days after heading [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation